-2a+3=9

Simple and best practice solution for -2a+3=9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2a+3=9 equation:


Simplifying
-2a + 3 = 9

Reorder the terms:
3 + -2a = 9

Solving
3 + -2a = 9

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-3' to each side of the equation.
3 + -3 + -2a = 9 + -3

Combine like terms: 3 + -3 = 0
0 + -2a = 9 + -3
-2a = 9 + -3

Combine like terms: 9 + -3 = 6
-2a = 6

Divide each side by '-2'.
a = -3

Simplifying
a = -3

See similar equations:

| 3(0)-9(3)=15 | | 2n-5=4n-7 | | 48=4n-4 | | 8a+18=6a+30 | | 4x^2+378x-4248.5=0 | | 8k=1 | | z/3=19=25 | | 10z-6=14 | | sin(3x)+cos(6x)=1 | | 8a-18=6a+30 | | 3v-5=8 | | k/2-1=1 | | (11x)+(6x+5)=180 | | 2=3d-4 | | 4z-7=9 | | 5a-6=56 | | f(x)=2x^2+6x-1 | | 20=x+x*0.2 | | 6x=(8-0.25x)-(6-0.75) | | 7x+11=3*4+2 | | 100+20a=220 | | 5a+6= | | 2x+7*3=22*3+x | | 9(y+1)(y+1)-9=0 | | 4(y-1)(y-1)-9=0 | | .4*x+.6*8=9.5 | | 11g+3=12g | | -17-2a=1 | | -4+17(x)=183 | | -5x+y=-7 | | x-14=x+15 | | 9b+40=3b |

Equations solver categories